Pengaruh Lokasi dan Harga Produk terhadap Loyalitas melalui Kepuasan Mahasiswa sebagai Mediasi: Analisis SMART PLS dalam Perspektif Manajemen Kantin Universitas Dinamika Bangsa - Candra Candra; Jasper Imanuel; Kotali Kotali; Michael Dylan; Stevani Putri Anggraini; Selaras Winny Br Marpaung; Violin Patricia; Yossinomita, Yossinomita (LPPM STIKOM Dinamika Bangsa, 2026)
This study aims to analyze the influence of location and product price on student loyalty through student satisfaction as a mediating variable in the context of cafeteria management at Universitas Dinamika Bangsa. A quantitative approach was employed, with data processed using the SmartPLS application. The sampling technique applied was purposive sampling, targeting active students who regularly utilize cafeteria services. A total of 100 respondents participated by completing an online questionnaire consisting of 13 items covering location, product price, satisfaction, and loyalty. The results reveal that: (1) location has a positive and significant effect on student satisfaction; (2) product price also shows a positive and significant effect on student satisfaction; and (3) student satisfaction significantly mediates the relationship between location, product price, and student loyalty. These findings highlight the strategic role of student satisfaction in fostering loyalty. Therefore, cafeteria management should emphasize strategic improvements in location and competitive pricing to enhance satisfaction, which in turn can strengthen sustainable loyalty among students.